1987
DOI: 10.1089/aid.1987.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV) Infection in Brains with AIDS-Related Leukoencephalopathy

Abstract: In addition to central nervous system (CNS) opportunistic infections and neoplasms, patients with acquired immunodeficiency syndrome (AIDS) develop unexplained dementia and encephalopathy and degeneration of the white matter. We studied autopsied brains from 20 adult patients who expired from AIDS to determine the relationship of human immunodeficiency virus (HIV) infection to white matter lesions and to clinical findings. In four patients with dementia/encephalopathy and abnormalities of the white matter, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…In the rhesus macaque simian immunodeficiency virus (SIV) model, both neurotropic and neurovirulent SIV MAC variants have been described (11,22,38). It is therefore suspected that specific neurotropic and neurovirulent HIV-1 variants exist and are associated with dementia.CCR5-using HIV-1 strains are predominant in the brain (13), and CCR5 ϩ perivascular macrophages and microglia are the cell types most frequently infected (19,35,37,43,49,50). The role of other cell types resident in the brain is less clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the rhesus macaque simian immunodeficiency virus (SIV) model, both neurotropic and neurovirulent SIV MAC variants have been described (11,22,38). It is therefore suspected that specific neurotropic and neurovirulent HIV-1 variants exist and are associated with dementia.CCR5-using HIV-1 strains are predominant in the brain (13), and CCR5 ϩ perivascular macrophages and microglia are the cell types most frequently infected (19,35,37,43,49,50). The role of other cell types resident in the brain is less clear.…”
mentioning
confidence: 99%
“…CCR5-using HIV-1 strains are predominant in the brain (13), and CCR5 ϩ perivascular macrophages and microglia are the cell types most frequently infected (19,35,37,43,49,50). The role of other cell types resident in the brain is less clear.…”
mentioning
confidence: 99%
“…Several early reports demonstrated HIV RNA or proteins in brain endothelial cells in autopsy material from patients with AIDS dementia but this ®nding has not been universal (Kure et al, 1990;Rostad et al, 1987;Smith et al, 1990;Wiley et al, 1986). Moses et al have demonstrated productive infection of cultured human brain microvessel endothelial cells by HIV-1 (Moses et al, 1996.…”
Section: Viral Contributions To Aids Dementiamentioning
confidence: 99%
“…This could occur either by direct infection of the EC leading to viral spread into the CNS (Wiley et al, 1986;Rostad et al, 1987;Rao et al, 1993) or by cytokineinduced damage to the blood-brain barrier which may allow the passive entrance of infected cells or viruses (Genis et al, 1992). Vascular alterations have been observed in AIDS-related encephalopathies in human (Smith et al, 1990;Hall et al, 1991 ;Briistle et al, 1992;Burns, 1992;Gray et al, 1993;Power et al, 1993) as well as in cats (Hurtrel et al, 1992).…”
mentioning
confidence: 99%
“…Vascular alterations have been observed in AIDS-related encephalopathies in human (Smith et al, 1990;Hall et al, 1991 ;Briistle et al, 1992;Burns, 1992;Gray et al, 1993;Power et al, 1993) as well as in cats (Hurtrel et al, 1992). Several studies revealed the presence of HIV in different cell types, especially in macrophages and microglial cells (Koenig et al, 1986;Parravicini et al, 1989;Briistle et al, 1992;Geleziunas et al, 1992), but also more rarely in astrocytes (Epstein et at., 1985;Mirra & del Rio, 1989), oligodendrocytes (Gyorkey et al, 1987) and EC (Wiley et al, 1986;Pumarola-Sune et al, 1987;Rostad et al, 1987;Ward et al, 1987;Wiley & Nelson, 1988;Smith et al, 1990). Most often, virus-infected microglial cells or macrophages were found in perivascular infiltrates in close contact with EC (Smith et al, 1990).…”
mentioning
confidence: 99%